A Review on Virtual Classroom - Maanvizhi, Saba; Jaiswal, Jiyaram Neha; Narayanan, Ravi Ram; Jain, Rajendra Rohit (Indian Journal of Pharmaceutical Education and Research, 2020)
A virtual classroom is an online learning method that is carried out via internet that provides communication for distance learner just like face-to-face classroom. This field of education is going to be in high trend in the upcoming days and soon will be replacing the traditional mode of education as internet dependent learning is growing rapidly in almost every schools and colleges. Two major forms of virtual classroom are synchronous and asynchronous. In virtual classroom it’s the choice of student to take synchronous form of learning or asynchronous form, if synchronous is selected the online teaching is scheduled which is led by a teacher and students can interact at same time and can get their queries solved at the same time even from remote area. In asynchronous form the learner attain their education at their own pace and at their convenient time and it is time independent which in turn is sought to control the order of activities. It is a great field as the students can clarify their doubts at any time from any place. One of the important goals of this application is to improve collaboration among teachers and students.
Keywords: Virtual classroom; Synchronous; Asynchronous; Education; Challenges